[Translated article] Modern Concepts in Melanocytic Tumors - A. Fernandez-Flores (Elsevier, 2023)
The advent of molecular pathology has fueled unprecedented advances in the diagnosis and understanding of melanocytic tumors. These advances, however, have also generated concepts that may be difficult to grasp for clinical practitioners, who are not always conversant with the array of genetic techniques employed in the laboratory. These same practitioners, however, are being increasingly called on to provide treatments that are often based on the latest molecular findings for melanocytic tumors. We review the most recent concepts in the pathway classification of melanocytic tumors, including intermediate lesions known as melanocytomas. We examine the genetic and molecular techniques used to study these tumors, look at where they overlap, and discuss their limitations and some of the most difficult-to-interpret results. Resumen: Con el desarrollo de la enfermedad molecular, el diagnóstico y la comprensión de los tumores melanocíticos ha experimentado un avance descomunal en los últimos años. Esto ha significado la aparición de conceptos de difícil asimilación en el mundo clínico, el cual no siempre está en contacto directo con las técnicas genéticas de laboratorio. Al mismo tiempo, sin embargo, al clínico se le está exigiendo una terapéutica basada en muchas ocasiones en los hallazgos moleculares más recientes de un tumor melanocítico. El presente artículo explora los conceptos moleculares más recientes de la clasificación en rutas patogénicas de los tumores melanocíticos, incluidas las formas intermedias conocidas como melanocitomas, y repasa las técnicas auxiliares usadas en el estudio de estos tumores, discutiendo los resultados más complejos, sus limitaciones y sus solapamientos.